The Trichoptera diversity of Nyungwe National Park, Rwanda, with description of a new species in the family Pisuliidae - Ngirinshuti, Leonce; Rukera Tabaro, Simon; Johanson, Kjell Arne (European Journal of Taxonomy, 2019)
A total of nine families of Trichoptera were identified from material collected in Malaise and light traps in the western part of Nyungwe National Park, southwestern Rwanda, late October 2018. Included in the material was an undescribed species of Pisuliidae which is described herein as Silvatares laetae Ngirinshuti & Johanson sp. nov. The new species adds to the six Pisuliidae species previously recorded for the East African region, five endemic to Tanzania and one to Uganda. This study portrays the first results of an ongoing survey on the Trichoptera fauna of Rwanda.